2013
DOI: 10.1155/2013/591520
|View full text |Cite
|
Sign up to set email alerts
|

Development ofEimeria nieschulzi(Coccidia, Apicomplexa) Gamonts and Oocysts in Primary Fetal Rat Cells

Abstract: The in vitro production of gametocytes and oocysts of the apicomplexan parasite genus Eimeria is still a challenge in coccidiosis research. Until today, an in vitro development of gametocytes or oocysts had only been shown in some Eimeria species. For several mammalian Eimeria species, partial developments could be achieved in different cell types, but a development up to gametocytes or oocysts is still lacking. This study compares several permanent cell lines with primary fetal cells of the black rat (Rattus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The investigation of enzymes was not in the focus of this study, but the FITC-cadaverine staining supports the assumption after analyzing the amino acid sequence of EnOWP13. Transglutaminase inhibitors, like cystamine, could shed more light in the role of transglutaminase activity in the wall formation process, but the in vitro growth of E. nieschulzi gamonts is complex and a reliable cultivation of small intestinal organoids from rats has not been described yet (Chen et al 2013). In gamont stage-specific transcript data of Eimeria, no transglutaminase is annotated yet, but a C2 domain-containing protein with a transglut-core unit (Gene ID ETH_00002295) can be found.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of enzymes was not in the focus of this study, but the FITC-cadaverine staining supports the assumption after analyzing the amino acid sequence of EnOWP13. Transglutaminase inhibitors, like cystamine, could shed more light in the role of transglutaminase activity in the wall formation process, but the in vitro growth of E. nieschulzi gamonts is complex and a reliable cultivation of small intestinal organoids from rats has not been described yet (Chen et al 2013). In gamont stage-specific transcript data of Eimeria, no transglutaminase is annotated yet, but a C2 domain-containing protein with a transglut-core unit (Gene ID ETH_00002295) can be found.…”
Section: Discussionmentioning
confidence: 99%
“…Eimeria mitis , one of the seven species of chicken coccidia, was first described by Tyzzer in 1929 [17] and considered to be relatively less pathogenic [18] [21] . Successful genetic complementation of other Eimeria species including Eimeria acervulina , Eimeria maxima , and Eimeria praecox , as well as the rat-specific Eimeria nieschulzi [22] [24] , support the potential use of less pathogenic species as vectors to develop novel vaccines [4] . Additionally, different intestinal localizations of the seven Eimeria species that infect chickens may have great implications in the performance of various Eimeria species as vaccine vector.…”
Section: Introductionmentioning
confidence: 95%
“…E. bovis , E. ovinoidalis , E. ninakohlyakimovae ) have shown that the parasite can develop to various stages (merozoites I and a few gametocyte-like stages) in several cell types, including bovine, human and porcine endothelial cell lines, bovine foetal gastrointestinal cells, bovine kidney epithelial cells and African green monkey kidney epithelial cells [ 28 32 ]. More particularly, the development of E. nieschulzi macrogamonts and oocysts were observed when cultured with mixed cells derived from inner fetal organs [ 32 ]. Here, we show similar levels of parasite invasion and development to the first generation of schizont in bovine epithelial-like kidney (MDBK), murine intestinal epithelial (m-IC cl2 ) and avian epithelial (CLEC-213) cells.…”
Section: Discussionmentioning
confidence: 99%